Citation of Law as a Legal Argument in an Early 11th-Century Breve From Farfa - Maskarinec, Maya (Reti Medievali Rivista, 2021)
In 1008 the notary Guido redacted a breve recording the renunciation of property by a certain Raino in favor of the monastery of Farfa (RF no. 476). Cited in this breve is a Lombard law (Liutprand 6), which allowed for deathbed donations. This article argues that this citation entailed an implicit legal argument, by the notary Guido and the Farfa monks who benefitted from the transaction, for the validity of Raino’s renunciation. When this is set in the context of the larger corpus of late tenth- to early-eleventh-century brevia preserved in Farfa’s register, what emerges is an ongoing attempt by notaries in the Sabina to find legal solutions that would facilitate transactions to the benefit of the Farfa monastery.